Prenatal and Postpartum Care Experiences During COVID-19 Pandemic Among Mothers in Denpasar - Ika Widi Astuti; I Gede Ngurah Harry Wijaya Surya (Babali Publisher, 2023)
Pregnant women generally report hesitation and reluctance in visiting health care providers to acquire prenatal care due to fear of SAR-Cov2 infection. The habit and culture of prenatal care among pregnant women influence the final pregnancy outcome. This study aimed to explore experiences of pregnancy, postpartum, and newborn care among the mothers, and also to provide basics in developing nursing care programs for pregnant women, postpartum care, and newborn care, responding to the new normal era adequately. This was a qualitative study with a phenomenology design. In-depth interview sessions involving 12 participants with a history of pregnancy and childbirth from March 2020 to March 2021 were conducted in Denpasar City. Collaizi model enrolled for the data analysis. Three themes surfaced during the data analysis: mothers’ feelings toward their pregnancy experience during the pandemic, health care services expected from the health professionals, and social supports during the pregnancy and postpartum period. These findings may present contributions to the organization of health information and maternity care service: pregnancy, postpartum, and newborn care, with more convenient access and delivered during the visitation of the health care providers.